Faktor Yang Mempengaruhi Keputusan Wanita Untuk Bekerja di Kecamatan Limo Kaum Kabupaten Tanah Datar - Novan Kharido; Efni Cerya (Jurnal Salingka Nagari, 2023)
This study aims to determine the determinants of women's decisions to work in the Limo Kaum sub-district, the analysis technique used is Logistic Regression Analysis was used to discover which characteristics had the most effect on female employees' willingness to work in both formal and informal settings sectors in conducting research on several variables. Often obtained variables that are descriptive quantitatif. With the dependent variable is binary, logistic regression analysis is useful for determining the influence of independent factors on the dependent variable. Results of research, (1) the age factor had a insignificant and negative effect in response to a woman's decision to work, (2) the education level factor had a significant and positive effect in response to a woman's decision to work, (3) the husband's income factor has a insignificant and positive effects in response to a woman's decision to work, (4) the household expenditure factor have a significant and positive effect on a woman's decision to work